Comparison of Three Methods for Lip Print Analysis: Lipstick, Latent, and Digital Photography for Sex Determination and Permanency Assessment Over Time - Sumanta K. Kolay; Rohit Sharma; Ajit K. Chaudhary; M. K. Sunil; Swapan K. Purkait; Pradeep K. Jha (Journal of Pharmacy and Bioallied Sciences)
Background: Lip print analysis, also known as cheiloscopy, is a valuable tool in forensic science for personal identification and sex determination. Methods: A total of 116 individuals (58 males and 58 females) were enrolled in this study. Lip prints were obtained using three methods: lipstick application, latent print development, and digital photography. The obtained lip prints were analyzed for accuracy, sex-specific variations, and stability over a 6-month period. Results: Lip print patterns exhibited significant differences between males and females across all three methods. The lipstick method demonstrated consistent and identifiable lip print patterns, with 25 males (43.1%) and 39 females (67.2%) displaying pattern 1. In contrast, the latent method showed less consistent results, with lip print pattern 1 observed in 25 males (43.1%) and 28 females (48.3%). Digital photography emerged as a promising alternative, offering detailed documentation capabilities, with pattern 1 observed in 30 males (51.7%) and 37 females (63.8%). However, no statistically significant association was found between lip print patterns and sex in the latent and digital methods. A longitudinal assessment revealed variations in lip print patterns over time, with some individuals showing changes in pattern distribution. Conclusion: These findings underscore the utility of lip print analysis in forensic science and emphasize the need for further research to enhance the interpretation of lip print evidence.